John Jacob Astor - Hubbard, Elbert, 1856-1915 (Salt Lake City, UT : Project Gutenberg, 1996)
"John Jacob Astor" by Elbert Hubbard is a biography written in the early 20th century that explores the life and achievements of John Jacob Astor, one of America's earliest and most influential entrepreneurs. The book chronicles Astor's journey from modest beginnings as the son of a butcher in Germany to becoming a wealthy fur trader and real estate mogul in America. It highlights themes of hard work, efficiency, and the importance of good habits in achieving success. The biography details Astor's early life, his migration to America, and his foray into the fur trade, where he quickly learned the business and established strong relationships with Native Americans. It depicts his innovative approach to both commerce and community, including his ventures in music and real estate. The text also underscores Astor's remarkable foresight in predicting the future growth of American cities, his community contributions, and his legacy through the establishment of the Astor Library. Hubbard emphasizes Astor's character, work ethic, and commitment to self-improvement, presenting him as a model of success through industriousness and strategic thinking. (This is an automatically generated summary.)
Series: Little Journeys to the Homes of the Great
Release date is 1996-01-01
Produced by Charles Keller
Keywords: Astor, John Jacob, 1763-1848; Businessmen -- United States -- Biography